A flexible network architecture for data multicasting in ?multiservice networks?. - Ravindran, K. (IEEE Journal on selected areas in communications)
The paper describes a canonical model of data-transport architecture that offers a flexible framework for implementations of data multicasting on backbone networks to support multiservice applications (e.g., videoconferencing, digital TV broadcast). The architecture is based on acyclic graph structured communication channels that provide connectivity among data sources and destinations through switches and links in a backbone network. The paper adopts a network-wide logical addressing of communication channels, which allows data multicasting to be realized on specific backbone networks by establishing local bindings between a logical address and the information on network-specific routing of data over switches and links. The approach allows various sources to share the switches and links in a multicast path connecting to destinations. This is a desirable feature in view of the significant reduction in network routing control costs and data transfer costs when dealing with high-volume multisource data (say, in videoconferencing). In addition, logical addressing allows grouping of selected destinations to overlay different ?virtual networks? on a base-level multicast channel (e.g., private discussion groups in a conference). As a demonstration of architectural flexibility, the paper describes the embedding of our multicast model on sample backbone networks capable of supporting multiservice applications: interconnected LANs, ATM networks, and high-speed public data networks (viz., SMDS networks)